India's Pink-Eye Mystery: Decoding the 2023 Conjunctivitis Outbreak - Paul, Tuhin James; Banga, Ayushreeya; Kaur, Ashmeen; Garg, Sonakshi; Singh, Amandeep (Infectious Disorders - Drug Targets, 2025)
The pink eye outbreak in 2023 was caused due to humid weather conditions in most regions of India. The most affected states include Delhi, Gujrat (21% cases), Maharashtra (30%), Himachal Pradesh (4%) and Karnataka (4%). The epidemiological data indicates that males have a high prevalence rate as compared to females; urban areas were most affected, and professionals as well as students were the population group that had the highest prevalence rate. The most common clinical manifestations were the presence of red eye, eye discharge, grittiness, and eyelashes being stuck together. One of the hallmarks of histopathology is a cobblestone formation of flattened nodules with central vascular centers. Conjunctivitis is a virus-mediated immune response accompanied by inflammation, which proceeds the immune reaction, giving rise to vasodilation, pseudo membrane formation, and conjunctivital discharge. The gold standard for the diagnosis of Conjunctivitis is the Adenoplus kit using PCR technology; apart from this slit lamp biomicroscope can be used for the evaluation. It is the need of the hour to spread awareness about the Pink Eye disease and the measures to prevent it.
Keywords: adenovirus